Device Characteristics of an 11.4% CZTSe Solar Cell Fabricated from Sputtered Precursors. Issue 16 (19th February 2018) - Taskesen, Teoman; Neerken, Janet; Schoneberg, Johannes; Pareek, Devendra; Steininger, Vincent; Parisi, Jürgen; Gütay, Levent
Abstract: Kesterite is an attractive material for absorber layers in thin film photovoltaics. Solar cells based on kesterite have shown a substantial progress over the last decade; nevertheless, further improvements in device efficiency are pending due to the open‐circuit voltage ( V oc ) deficit (i.e., difference between the maximum V oc that can be achieved according to Shockley–Queisser limit and actual V oc from the device). In this study, the optoelectronic properties of the author's internal record Cu2 ZnSnSe4 solar cell, which shows a power conversion efficiency of 11.4%, are presented. The device measurements reveal a V oc deficit of 337 mV, which is one of the lowest V oc deficits in the literature. Moreover, an unusual behavior for kesterite is observed: (i) photon energy of the photoluminescence emission and (ii) the extrapolated V oc for 0 K are both matching the band gap region of the absorber. These results indicate a significant improvement in the recombination characteristics and absorber quality in comparison to other kesterite devices in literature. Abstract : Optoelectronic properties of an 11.4% Cu2 ZnSnSe4 solar cell are presented. The device shows an unusual behavior for kesterite: (i) photon energy of the photoluminescence emission and (ii) the extrapolated V oc for 0 K are both matching the band gap region of the absorber. These properties lead to one of the lowest V oc deficits for kesterite in the literature.